2019
DOI: 10.1016/j.immuni.2019.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Stellate Cells, Hepatocytes, and Endothelial Cells Imprint the Kupffer Cell Identity on Monocytes Colonizing the Liver Macrophage Niche

Abstract: SummaryMacrophages are strongly adapted to their tissue of residence. Yet, little is known about the cell-cell interactions that imprint the tissue-specific identities of macrophages in their respective niches. Using conditional depletion of liver Kupffer cells, we traced the developmental stages of monocytes differentiating into Kupffer cells and mapped the cellular interactions imprinting the Kupffer cell identity. Kupffer cell loss induced tumor necrosis factor (TNF)- and interleukin-1 (IL-1) receptor-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
514
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(545 citation statements)
references
References 41 publications
25
514
4
2
Order By: Relevance
“…While CellPhoneDB predicts potential receptor-ligand interactions based on their expression on sender and receiver cells, it does not model the downstream transcriptional effects of these interactions. To integrate these downstream effects, we applied the NicheNet algorithm (Bonnardel et al, 2019;Browaeys et al, 2019) and focused the analysis on mono-like macrophages. First, we performed ligand activity analysis to prioritize ligands that could best predict the defined DE genes in mono-like macrophages ( Figure 6C and S6C).…”
Section: Amsmentioning
confidence: 99%
“…While CellPhoneDB predicts potential receptor-ligand interactions based on their expression on sender and receiver cells, it does not model the downstream transcriptional effects of these interactions. To integrate these downstream effects, we applied the NicheNet algorithm (Bonnardel et al, 2019;Browaeys et al, 2019) and focused the analysis on mono-like macrophages. First, we performed ligand activity analysis to prioritize ligands that could best predict the defined DE genes in mono-like macrophages ( Figure 6C and S6C).…”
Section: Amsmentioning
confidence: 99%
“…While our current data clearly demonstrate that Notch2 loss-of-function promotes macrophage development from Ly6C hi monocytes and a pro-inflammatory milieu during TLR stimulation, we have previously shown that Dll1-Notch signaling promotes maturation of anti-inflammatory macrophages from Ly6C hi monocytes in ischemic muscle (Krishnasamy et al, 2017). Furthermore, Dll4-Notch signaling initiated in the liver niche was recently shown to promote Kupffer cell development after injury (Johnny Bonnardel et al, 2019;Sakai et al, 2019) or to promote pro-inflammatory macrophage development (Xu et al, 2012). This suggests that the role of Notch is ligand-, cell-and context-specific, which emphasizes the differential effects of specific ligand-receptor combinations (Benedito et al, 2009).…”
Section: Discussionmentioning
confidence: 44%
“…Notch signaling is a cell contact-dependent signaling pathway regulating cell fate decisions in the innate immune system (Radtke, Macdonald, & Tacchini-Cottier, 2013). Notch signaling regulates formation of intestinal CD11c + CX 3 CR1 + immune cells (Ishifune et al, 2014), Kupffer cells (Johnny Bonnardel et al, 2019;Sakai et al, 2019) and macrophage differentiation from Ly6C hi monocytes in ischemia (Krishnasamy et al, 2017), but also development of conventional DCs (Caton, Smith-Raska, & Reizis, 2007;Epelman et al, 2014;Lewis et al, 2011), which is mediated by Notch2.…”
Section: Introductionmentioning
confidence: 99%
“…However, others were not. Bonnardel et al [129] generated RNA-seq data from purified liver sinusoidal endothelial cells (EC). We examined the profiles of the most highly-expressed EC genes in the macrophage dataset.…”
Section: Resident Macrophage Activation During Isolationmentioning
confidence: 99%